Chimeric Antigen Receptor (CAR)-NK92 cells effective against glioblastoma, breast- and pancreatic cancer in vitro and in a murine xenograft model of ovarian cancer - Abdelhadi Boulifa; Alexander Sebastian Franzén; Martin J. Raftery; Clarissa Radecke; Gabriele Pecher (Cancer Cell International)
Abstract Background Aggressive tumors such as glioblastoma, breast, ovarian and pancreatic cancer have low survival rates and new therapies are urgently needed. One potential target is CD44v6, a splice variant of CD44 that is associated with poor prognosis. Recently, NK cells expressing CAR molecules have shown promise in combining specific targeting of solid tumors with a low risk of side effects. The aim of the current study is to explore the efficacy of the CD44v6-CAR construct expressed in the NK cell line NK92 against solid tumors both in vitro and in vivo. Methods Flow cytometry was used to evaluate the expression of CD44v6 on glioblastoma, breast, ovarian and pancreatic cancer cell lines. In order to investigate the efficacy of CD44v6-CAR-NK92 against these solid tumors in 2D and 3D models, cytotoxicity was measured using a luminescent cell viability assay. Additionally, we assessed the levels of IFN-γ in cell culture supernatants using an ELISA method. Finally, we evaluated our therapeutic in vivo using a xenografted murine model of ovarian cancer through bioluminescent imaging. Results CD44v6-CAR-NK92 cells exhibit specific cytotoxicity against glioblastoma, breast, ovarian and pancreatic cancer after 24 h compared to the control, both in 2D and 3D models. Furthermore, the activity of CD44v6-CAR-NK92 was validated by quantifying specific cytokine release in response to target cells. Finally, we could show that CD44v6-CAR-NK92 was effective in reducing tumor burden in a xenografted murine model of ovarian cancer. Conclusion Our results demonstrate that CD44v6-CAR-NK92 cells could be an attractive therapeutic agent for the treatment of solid tumors.